The Oxford handbook of Buddhist practice - Arai, Paula Kane Robinson; Trainor, Kevin (Oxford University Press USA - OSO, 2022)
Popular representations of Buddhism often depict it as spiritual, disembodied, and largely devoid of ritual. Yet embodiment, materiality, emotion, and gender shape the way most Buddhists engage with their traditions. The essays within The Oxford Handbook of Buddhist Practice push beyond traditional representations of Buddhism as divided into static schools and traditions, highlighting instead the contested and negotiated character of individual and group identities. Given the fluidity and diversity of Buddhist practices, the question that animates this volume is: What makes a given practice Bu
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung; Ritus; Kultgegenstand; Buddhismus; Sādhana; Meditation